The Effect of Product Diversity, Brand and Price on Consumer Purchasing Decisions at PT. Indomarco Adi Prima Bengkulu - Arlina Arlina; Ermy Wijaya; Nurzam Nurzam (UNIVED Press, 2023)
The method used in this study is a questionnaire method with research instruments namely validity test, reliability test, multiple linear regression test, coefficient of determination test, t test, and f test, with the sample in this study as many as 80 respondents, with accidental sampling technique. The results show that multiple linear regression Y = a + b1X1 + b2X2 + b3X3 + e or Y = -1.489 + 0.161 (X1) + 0.069(X2) + 0.809(X3) + 1.072, meaning that there is a positive or unidirectional relationship to consumer purchasing decisions (Y) at PT. Indomarco Adi Prima. Meanwhile, the results of the partial test of the product diversity variable (X1) show tcount 2.641 > ttable 1.991 and a significance of 0.010 <0.05, then the hypothesis Ha is accepted and Ho is rejected, meaning that product diversity (X1) has a positive and significant effect on consumer purchasing decisions (Y). The results of the Brand test (X2) show a tcount value of 1.763 < ttable 1.991 and a significance of 0.085> 0.05, then the Ha hypothesis is rejected and Ho is accepted, meaning that the brand (X2) has no effect on consumer purchasing decisions (Y). The results of the price test (X3) show tcount 16,420 > ttable 1,991 and a significance of 0.000 <0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that the price (X3) has a positive and significant effect on consumer purchasing decisions (Y). Then the results of the simultaneous test, accept the hypothesis or accept Ha and reject Ho, meaning that there is an influence between product diversity (X1) brand (X2) and price (X3) on consumer purchasing decisions (Y) at PT. Indomarco Adi Prima Bengkulu amounted to 595,615. The results of multiple linear regression test that the regression coefficient between product diversity (X1), brand (X2) and price (X3) is positive, meaning that there is a positive or unidirectional relationship to consumer purchasing decisions (Y) at PT. Indomarco Adi Prima.